Family ownership during the Covid-19 pandemic - Amore, Mario Daniele; Pelucco, Valerio; Quarato, Fabio (Journal of Banking & Finance, 2022)
A growing literature is devoted to understand how companies react to major external shocks. Contributing to this research, we study how the presence of families in corporate ownership and leadership affected the reaction of firms to the Covid-19 pandemic. Using data from Italy, we find that family firms exhibited higher market performance and operating profitability than other firms during the pandemic period. This result is stronger for companies without relevant minority investors and with multiple family shareholders. Delving into the mechanisms, we show that the outperformance of family firms is driven by a more efficient use of labor and a lower drop in revenues. Collectively, our results expand existing research by showing how family ties shape the response to adverse events.